Pendidikan Agama Islam Penangkal Radikalisme - Nurhakiky, Sri Mulya; Mubarok, Muhammad Naelul (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2019)
Indonesia as a country that adheres to the understanding of a single bhinneka if it turns out it has not been able to demonstrate its resilience to minimize the radical and extreme attitudes of some of its religious adherents. Siltation of religion and fanaticism results in a sense of superiority over adherents of other religions. Religious radicalism causes violent actions caused by a partial interpretation of the concept of jihad in Islam, the logical consequence of this interpretation is the matching of terrorism as the fruit of radicalism. Radical ideology or understanding of radicalism has developed so rampant that it penetrates the boundaries of formal and non-formal education. This paper tries to reveal how the noble values of Islamic Religious Education (PAI) in preventing radical